Revisiting yield gaps and the scope for sustainable intensification for irrigated lowland rice in Southeast Asia - Silva, ‪João Vasco; Pede, Valerien O.; Radanielson, Ando M.; Kodama, Wataru; Duarte, Ary; Guia, Annalyn H. de; Malabayabas, Arelene Julia; Pustika, A.B.; Argosubekti, Nuning; Vithoonjit, D.; Pham Thi Minh Hieu; Pame, A.R.; et al. (Elsevier, 2022)
Recent studies on yield gap analysis for rice in Southeast Asia revealed different levels of intensification across the main ‘rice bowls’ in the region. Identifying the key crop management and biophysical drivers of rice yield gaps across different ‘rice bowls’ provides opportunities for comparative analyses, which are crucial to better understand the scope to narrow yield gaps and increase resource-use efficiencies across the region.